Savoirs mondains, savoirs savants : les femmes et leurs cabinets de curiosités au siècle des Lumières - Adeline Gargam (Genre & Histoire)
During the Enlightenment in France, curiosity culture constituted both a fashion and an intellectual and social game.  This article explores thirty cabinets of  curiosities run by women during this period. Wealthy women from the Parisiain and provincial aristocracy and middle classes organized cabinets in alchemy, mineralogy, physics and chemistry, natural history and biology studies. These cabinets can be divided into two distinct categories. The first represented amateur interests; they were developed for show and served as schools for intellectual and éducational pleasure. The second category were run by experienced women scientists who used their laboratories to conduct experimental research in the name of medical progress and public instruction. This article also describes how these private cabinets functioned, their composition, their interior décor as well as the contents of the collections, which required the organisation, acquisition and preservation techniques used in their male counterparts.